Visualizing the mass transfer flow in direct-impact accretion - Frank, Juhan; Straub, Alexander; Shiber, Sagiv; Amini, Parsa; Marcello, Dominic C; Diehl, Patrick; Ertl, Thomas; Sadlo, Filip; Frey, Steffen (Monthly notices of the Royal Astronomical Society, 2025)
We use a variety of visualization techniques to display the interior and surface flows in a double white dwarf binary undergoing direct-impact mass transfer and evolving dynamically to a merger. The structure of the flow can be interpreted in terms of standard dynamical, cyclostrophic, and geostrophic arguments. We describe and showcase some visualization and analysis techniques of potential interest for astrophysical hydrodynamics. In the context of R Coronae Borealis stars, we find that mixing of accretor material with donor material at the shear layer between the fast accretion belt and the slower rotating accretor body will always result in some dredge-up. We also discuss briefly some potential applications to other types of binaries.